Right person in the right place: How the host country IPR influences the distribution of inventors in offshore R&D projects of multinational enterprises. (6th September 2015) - Nandkumar, Anand; Srikanth, Kannan
Abstract : Research summary : Prior work has shown that the strength of the intellectual property regime (IPR) in a host country influences offshore R&D to that country. Building on this work we propose that the strength of the IPR in a host country differentially influences the threat of knowledge leakage on projects that are produced for the location where the multinational firm is headquartered (home) versus the offshore location to which the R&D project is sent (host). We argue and show that when the host location has a weak IPR, fewer host inventors are involved in host R&D projects when compared to home R&D projects. We test our hypotheses using a dataset of patents held by US assignees, but coinvented in 43 host locations with differing IPR strength . Managerial summary : Multinational enterprises often cite the weak IPRs at emerging economy host destinations as a significant impediment to offshore R&D activities in those countries, despite the abundant supply of inexpensive scientific talent there. We find that the weak IPR at the host destination is a greater impediment to offshore R&D that is aimed for end use at the host market than for R&D that is aimed for end use globally or in the home market. Since IPRs are local, a weaker IPR at the host location does not protect IP that is relevant to the host market. Since the IPR at the home country is more relevant for technologies aimed at the home market, the IPR at the host country is irrelevant for such R&D projects . Copyright © 2015 John Wiley & Sons, Ltd.